In Vitro Studies of Genistein Lipophilic Derivatives as Potential UV Radiation Protectors - Magdalena Skonieczna; Kinga Plasa; Ewa Borowska; Agata Jakubowska; Wiesław Szeja; Anna Kasprzycka (MDPI AG, 2024)
The major environmental factor responsible for skin cancer is ultraviolet (UV) radiation, present in sunlight. UV radiation is directly linked to the production of reactive oxygen species (ROS), which accumulate in exposed cells and cause serious damage. The antioxidant systems present in cells cannot always sufficiently neutralize the ROS. Therefore, supplementation with exogenous antioxidants has been proposed. The antioxidant properties of some isoflavones, such as genistein, have already been well-proven. Genistein has limited bioavailability. However, its derivatives, with increased lipophilicity, could facilitate its transfer into cells, where they can expose its antioxidative potential. This study aims to investigate three genistein derivatives, with greater lipophilicity than the native compound, regarding their cytotoxicity, antioxidative properties, and effect on the cell cycle in normal human dermal fibroblasts (NHDF) and a melanoma cancer cell line (Me45). Results showed that lipophilic modification of the genistein molecule changes the biological response of NHDF and Me45 cell lines to UV-C radiation, but the lipophilicity cannot be directly linked with the activity of the compounds. A comparison of the effects of the genistein derivatives on healthy and cancerous cells suggests that their mode of action strongly depends on the type of cell involved.